B, Model Pembelajaran Discovery Learning Untuk Meningkatkan Motivasi dan Hasil Belajar Siswa pada Masa Pandemi Mata Pelajaran Bahasa Bali SMP Negeri 6 Mengwi: Pendekatan Inovatif dalam Pembelajaran Bahasa Bali di Tengah Pandemi - Sujana, I Gede; Trisna Dewi, Komang (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2025)
Globalization affects the shift of local culture which is the identity of a community group. This has been proven by the existence of Balinese language, which is experiencing challenges of degradation from time to time. Based on these problems, PC KMHDI Denpasar tried to implement the KMHDI’s Rumah Daya Program as a forum for grounding Balinese language and preserving local culture at SD Saraswati 6 Denpasar. Although it has been implemented, there is no concrete explanation regarding the success of the KMHDI’s Rumah Daya program implementation. Therefore, the purpose of this research is presented to analyze and answer three formulations of program problems, which are related to the urgency, essence, and implications of the program on the earthing of Balinese Language in SD Saraswati 6 Denpasar. In terms of methods, this research uses descriptive qualitative data with a naturalistic-based approach. Data sources came from primary and secondary sources. Primary data were obtained through observation of activities and interviews with research subjects, namely teachers and students, and secondary data were obtained through literature studies and documentation as reinforcement. The data were analyzed using the Miles and Huberman approach. The results showed that KMHDI's Rumah Daya program is able to be the answer to ground the Balinese language in the school environment interactively. In conclusion, this program is able to provide positive implications, both as an interactive learning space, a space for preserving the nation's culture, and a space for learning while playing that is useful